Systematic analysis of prognostic and immunologic characteristics associated with coronavirus disease 2019 regulators in acute myeloid leukemia - Shi, Mingjie; Chen, Lidan; Wei, Yue; Chen, Riling; Guo, Runmin; Luo, Fei (Frontiers in Genetics, 2022)
The Coronavirus disease 2019 (COVID-19) pandemic has so far damaged the health of millions and has made the treatment of cancer patients more complicated, so was acute myeloid leukemia (AML). The current problem is the lack of understanding of their interactions and suggestions of evidence‐based guidelines or historical experience for the treatment of such patients. Here, we first identified the COVID-19 related differentially expressed genes (C-DEGs) in AML patients by analyzing RNA-seq from public databases, and explored their enrichment pathways and candidate drugs. A total of 76 C-DEGs associated with the progress of AML and COVID-19 infection were ultimately identified, and the functional analysis suggested that there are some shared links between them. And their protein-protein interactions (PPI) and protein-drug interactions were then recognized by multiple bioinformatics algorithms. Moreover, a COVID-19 gene-associated prognostic model (C-GPM) with riskScore was constructed, patients with high-riskScore had poor survival and apparently immune-activated phenotypes, such as stronger monocyte and neutrophils cell infiltrations and higher immunosuppressants targets expressions, meaning which may be one of the common denominators between COVID-19 and AML and the reason what complicates the treatment of the latter. These findings visualized those C-DEGs’ enrichment pathways and inner associations, and the C-GPM based on them could accurately predict survival outcomes in AML patients, which all will be helpful for further optimizing therapies for AML patients with COVID-19 infections.